Social Commerce 2.0: TikTok Shop dan Masa Depan Belanja Digital - Zulfan Zulkarnaen Z; Agus Hermawan (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The development of digital technology has given birth to a new era in the world of electronic commerce, namely social e-Commerce 2.0, which combines interactive features of social media with the ease of online transactions. One of the pioneers of this transformation is TikTok Shop, a platform that allows users to explore, promote, and purchase products directly through short video content. This article discusses how TikTok Shop revolutionizes the way consumers interact with products, the role of content creators as the main driver in marketing, and relevant business strategies amidst changes in digital consumer behavior. Through a trend analysis approach and case studies, this article examines the potential and challenges faced by TikTok Shop as a representation of the future of digital shopping. The results of the discussion show that TikTok Shop not only accelerates the buying and selling process but also creates a new ecosystem that combines entertainment, community, and consumption in one integrated platform.